DAMPAK PERILAKU PENGAMBILAN RISIKO TERHADAP KINERJA KEUANGAN DI INDONESIA - Fadli, Syavira; Satria, Doni (Universitas Negeri Padang, 2025)
This research aims to analyze the impact of risk-taking behavior on the financial performance of banks in Indonesia. The stability and profitability of banks are key indicators in assessing the health of the banking sector, where Return on Assets (ROA) is used as the primary measure of financial performance. The data used in this study is sourced from banking annual reports, Bank Indonesia (BI), and the Financial Services Authority (OJK) during the period of 2007–2023. The analysis method applied is Generalized Ordered Logistic Regression to classify the levels of ROA of banks and identify the impact of risk-taking behavior.